Perianesthesia management of chylothorax and severe obserity with sternotomy under general aneshesia and anemia: A case report - Suandika Made; Handayani Rahmaya Nova; Sumarni Tri; Maharani Cindy; Dani Dwi Darmawan; Sulaeman Ahmad (BIO Web of Conferences)
Surgery with Chylothorax cases is increasingly common. Chylothorax can result in high morbidity and mortality. Effective perianesthesia measures are crucial for managing hemodynamic instability, including hypertension and anemia, and for selecting suitable anesthetic agents to ensure successful surgery. This case focuses on perianesthesia management in Chylothorax surgery involving Sternotomy, addressing issues of hypertension and anemia. The study results indicate that the patient experienced oxygen saturation decline and hemodynamic instability, necessitating adjustments in anesthetic administration. During the recovery phase, the patient required continued ventilatory support and ongoing monitoring due to prolonged effects of anesthetic drugs. In conclusion, anesthesia management in patients with chylothorax and severe obesity requires careful planning and coordination between the surgical and anesthesia teams to ensure respiratory and hemodynamic stability throughout the surgery.